From traditional remedy to modern medicine: Review of the genus Euphorbia - Mahmoud Dogara, Abdulrahman; Bussmann, Rainer W (Ethnobotany Research and Applications, 2026)
Background: Plants have been used in human medicine since ancient times. Natural products continue to play a crucial role in the drug discovery process. Genus Euphorbia is widely known for its therapeutic properties all over the world. We aim to update traditional medicinal uses, chemical composition, pharmacological activities and clinical trial of Genus Euphorbia. Methods: Data pertinent to the genus Euphorbia and its distinctive compounds were obtained from globally recognized scientific databases and esteemed publications via online platforms, including Web of Science, PubMed, MDPI, Springer Nature, Wiley Online Library, and Elsevier. The inquiry utilized the term “Euphorbia” alongside the following terms: “phenolic compounds,” “flavonoids,” “terpenoids,” “alkaloids,” “phenylpropanoids. Results: Traditionally, the genus is used to treat skin diseases, cancer, diabetes, hypoglycemia, healing wounds, toothache. Four hundred and two compounds (402) were identified across the genus with dominant diterpenoids, triterpenoids, flavonoids and phenols. Compounds were found to be active against cancer cells, viruses, microbes and inflammation. Clinical trial show members of the genus to be effective against hemorrhoids, varicose veins, human nonmelanoma skin cancers, dengue and cracked feet. Conclusions: The genus Euphorbia is a highly potential avenue of pharmacognostic research and drug discovery based on secondary metabolites. It has a vast chemical repertoire of various terpenoid compositions, which provides a good source of chemically diverse and clinically important compounds. It is also essential to conduct structure-activity relationship studies to determine the molecular characteristics that endow activity and to provide a means of rationally developing new derivatives. Keywords: Compound, Euphorbia, Clinical trial, Plants